The Effects of Soil Amended with Solid Fibrous Waste on The Morphological Quality of Oil Palm (Elaeis guineensis Jacq.) Seedling - Sylvia Madusari (Journal of Applied Sciences and Advanced Technology, 2018)
Organic materials as industrial by-products are potentially used as alternative growth media composites with the aim of reducing the use of top soil and improving the quality of plants in the nursery. Mesocarp of palm fruit (fiber) and coconut fiber powder (cocopeat) are rich in plant nutrients. Composting of these by-products will be helpful in recycling and re-use of biodegradable waste useful for growing media. This research use Completely Randomized Design (CRD) one factor consist of 4 treatment. The treatment were (a). P0 = sub soil 100% (control), (b). P1 = 50% mesocarp fiber composts + 50% sub soil, (c). P3 = 50% cocopeat composts + 50% sub soil, and (d). P3 (mesocarp fiber 1 kg + cocopeat fiber 0.5 kg + 0.5 kg cattle dung) composts + sub soil 50 %. Growing media that consists of 50% mesocarp fiber and 50% sub soil (P2) was suitable as growing medium in early seedling. Compost of mesocarp fiber has the content of C-organic 52,28%, N 1,37%, C / N ratio 38,11%, P2O5 0,47%, K2O 0,89%, Mg 0,23%. The use of composted mesocarp fiber media mixed with 50% sub soil showed significant effect on the growth of seed diameter of oil palm seedlings at age 3 MAP.